Peran Ibu dalam Perubahan Sosial Keluarga dan Komunikasi Keluarga di Daerah Terdampak COVID - 19 - Riski Damastuti (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
COVID-19 causes various changes in society, both social, economic, and cultural changes. This study examines COVID-19 from the perspective of women and families. This study is a qualitative study that aims to determine the role of mothers in family social change and family communication during the pandemic. From the results of the study, it is known that mothers have a fairly important role in dealing with social changes during the Pandemic and become an important agent of socialization related to COVID-19 information. Mother's competence in processing information is one of the most important skills, related to the number of COVID-19 hoaxes circulating on social media. In addition to the mother's competence in processing information, it is also necessary to have the mother's competence in conveying information to the family. The delivery of communication cannot be done in the same way, because each family member has their own uniqueness.